Effectiveness Of Nurse Led Strategies to Prevent Delirium Among Critically Ill Patients Admitted in Intensive Care Unit - R, Renuka; S, Nalini; Manjula, Manjula; Renuka, Renuka; Hemalatha, Hemalatha (Journal of Neonatal Surgery, 2025)
Introduction: Delirium, characterized by sudden impairment in consciousness and cognition, is prevalent among critically ill patients, especially in ICU settings, with rates up to 80%. It significantly impacts patient outcomes, including increased mortality, extended hospital stays, and higher healthcare costs. Despite its severity, delirium often goes unrecognized and untreated due to inadequate screening. This study aims to evaluate the effectiveness of nurse-led interventions in reducing delirium in ICU patients and to explore the relationship between delirium and various background variables. Methods: A quantitative research approach was employed using a quasi-experimental design with a non- randomized pretest-posttest control group. The sample consisted of 80 critically ill patients selected through non-probability sampling. These patients were divided into study and control groups of 40 each. The Confusion Assessment Method for the ICU (CAM-ICU), developed by Wesley Ely in 2001, was used to measure delirium. Initial data collection occurred on the first day, including a pretest to assess background variables and delirium levels. The study group received nurse-led interventions—four sessions of 45 minutes each over four days—alongside routine care. Post-tests were conducted on Days 1, 2, 3, and 4 following the intervention. Results: In the study involving 80 critically ill patients, the study group (n=40) and control group (n=40) both showed no delirium at baseline. By Posttest 1, 5% of the study group had mild to moderate delirium versus 22.5% in the control group (p=0.02). By Posttest 2, 7.5% of the study group had mild delirium compared to 32.5% in the control group (p=0.001). At Posttest 3, the study group had only 2.5% with mild delirium and no severe cases, whereas 52.5% of the control group experienced mild delirium and 5% had severe delirium (p<0.001). Statistical analyses confirmed significant reductions in delirium scores in the study group compared to the control group over time. Conclusion: The study revealed that nurse-led interventions effectively reduced delirium scores among critically ill ICU patients, with the study group showing a consistent decline in delirium, reaching median scores of zero, whereas the control group experienced a worsening of delirium severity over time. These results highlight the critical role of targeted interventions in managing delirium and enhancing patient outcomes in intensive care.